Use of prosthesis material in inguino/ crural hernias and their failure. - Croci, Fabio; Gastambide, Carmelo; Terra, Eneas (Cirugía del Uruguay, 1984)
Authors present their personal experience in the use of prosthesic material in the surgery of inguino-crural hernias and their failure as applied to a series of 140 cases, 73 of which were failures and among them, 24 reci• divous hernias. Complication rate was 4,2% ·and the failure rate was 5%. The material used in most cases (90%) was the Marlex mesh.